2017
DOI: 10.1103/physrevlett.118.221801
|View full text |Cite
|
Sign up to set email alerts
|

Nonmaximal θ23 Mixing at NOvA from Neutrino Decoherence

Abstract: In a study of a muon-neutrino disappearance at 810 km, the NOvA experiment finds flavor mixing of the atmospheric sector to deviate from maximal (sin^{2}θ_{23}=0.5) by 2.6σ. The result is in tension with the 295-km baseline measurements of T2K, which are consistent with maximal mixing. We propose that θ_{23} is in fact maximal, and that the disagreement is a harbinger of environmentally induced decoherence. The departure from maximal mixing can be accounted for by an energy-independent decoherence of strength … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 34 publications
(61 reference statements)
1
24
0
Order By: Relevance
“…[13,14] a solution to the LSND anomaly based on quantum decoherence, compatible with global neutrino oscillation data, was proposed. More recently, in [17] it was shown that the ∼ 2σ tension between T2K and NOvA on the measurement of the atmospheric mixing angle θ 23 could be alleviated through the inclusion of decoherence effects in the atmospheric neutrino sector, namely, γ 23 = (2.3 ± 1.1) · 10 −23 GeV. Such value of γ 23 would be close to the SK bound from ref.…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations
“…[13,14] a solution to the LSND anomaly based on quantum decoherence, compatible with global neutrino oscillation data, was proposed. More recently, in [17] it was shown that the ∼ 2σ tension between T2K and NOvA on the measurement of the atmospheric mixing angle θ 23 could be alleviated through the inclusion of decoherence effects in the atmospheric neutrino sector, namely, γ 23 = (2.3 ± 1.1) · 10 −23 GeV. Such value of γ 23 would be close to the SK bound from ref.…”
Section: Introductionsupporting
confidence: 70%
“…In particular, we find that the reference value for γ 23 considered in ref. [17] to explain the small tension previously reported between NOvA and SK data is indeed already excluded by IceCube data. Regarding the cases with n = 1, 2, we find that the sensitivity of IceCube is particularly strong.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…But there are two many nuisance parameters in this issue. The angular K + production parameter [73], the non-standard interaction effects [40,86] and the unknown ν e interference might all count.…”
Section: Keepmentioning
confidence: 99%